PEMODELAN REGRESI DATA PANEL PADA TINGKAT PARTISIPASI ANGKATAN KERJA PEREMPUAN DI PROVINSI KALIMANTAN SELATAN - Putri Norhikmah; Fuad Muhajirin Farid; Aprida Siska Lestia (Universitas Lambung Mangkurat, 2022)
Women’s Labor Force Participation Rate (LFPR) is an indication that can shows how much participation of women in the process development. The purpose of this study is to provide an overview of LFPR women in the Province of South Kalimantan, explaining the expected variables influence on women’s LFPR in South Kalimantan Province and determine the best model. This research data is sourced from the Centra Statistics Agency of South Kalimantan Province with a time period of 2017-2020. Variable independen research, namely female workers, female residents who are still in school and taking care of the household, the average length of schooling for women, female population according to the highest education ever graduate from senior high school above, female household heads, status of married and unmarried women marriage, district/city minimum wage, human development index women and regional domestic income growth at constant prices while the dependent variable is female LFPR. The results of data analysis, can be conclude that the Fixed Effect Model as the best model of panel regression. Women’s LFPR in South Kalimantan Province by producing two recommendation with Fixed Effect Model an R-Squared in the first model of 99,40%.Keywords: Women’s LFPR, Panel Data Regression, South Kalimantan